Best Practice BRT for Increase TransJakarta Modal Share - Adhi Muhtadi; Indrasurya B. Mochtar; Hera Widyastuti (Institut Teknologi Sepuluh Nopember, 2017)
TransJakarta since 2004 was expected as the backbone of the public transportation in Jakarta as well as TransMilenio in Bogota. However, the role of TransJakarta only approximately 1, 95% of the overall number of trips has reached 19 million/day. The analysis technique on this paper is descriptive analysis. TransJakarta operational perceived is still not effective, so that the necessary efforts to increase modal share sourced from BRT management best practice in other countries. Efforts could be made to increase modal share, among others, the elimination of thousands of parking and replaced by pedestrian friendly also develop a separate bike lane along 303 km in Bogota (Colombia). TransJakarta operational is still considered less in some aspects that are: total of fTransJakarta fleet, total of feeder route, Transjakarta speed and headway still need improved, overtaking lanes are built along the TransJakarta route, Integration with all public transport is absolutely necessary, integration with pedestrians and bicycle users TransJakarta ticket fares should be integrated with feeder and other public transportation such as KRL, city buses and paratransit and using smartcards. In terms of restrictions on the use of private vehicles can be done in the following ways implement a bike-sharing program, implement program of not using motor vehicles during weekdays for 1 day in a week, providing park and ride, implement fuel restriction program for gasoline purchases, implement car sharing program. If the operational performance of TransJakarta has been improved and restrictions on the use of private motor vehicles are implemented, it is expected that the modal split of road users in Jakarta can be expected to rise to be more ideal. In some other parts of the world some experts say ideal conditions of split capital between public transport and private vehicles can reach 65%: 35%. Hopefully the city of Jakarta can achieve this.